EXTENT OF UTILIZATION OF TECHNOLOGICAL FACILITIES IN TEACHING AND LEARNING IN PUBLIC PRIMARY SCHOOLS IN ANAMBRA STATE. - Obidike, Ngozi Diwunma; OKEKE, Goodness Chukwuemeka (Journal of Early Childhood and Primary Education, 2025)
The aim of this study is to ascertain the extent of utilization of Technological facilities in teaching and learning in public primary schools Anambra State. Four research questions guided the study. The study adopted the descriptive survey research design. The population of the study comprises of 8078 teachers in pubic primary schools in Anambra State. The sample size for the study is 807 using simple random sampling technique. A four point rating scale containing 30 items was used for data collection. This instrument was validated by three experts. Technological Facilities Utilization Questionnaire (BTIQ) was used to collect data. Cronbach Alpha method was used to establish the reliability of the instrument which yielded coefficients of 0.67, 0.62, 0.73 and 0.72 for the four clusters respectively with an overall reliability coefficient of 0.86. Mean and Standard Deviation were used for data analysis.  The finding of the study indicates that public primary school teachers in Anambra State utilizes technological facilities in their teaching to a moderate extent. Based on the finding, it was recommended that appropriate technology items which supports teaching and enhances learning should be provided and made easily accessible to teachers so as to foster better academic performance for pupils, among others. Futher findings reveals that retraining of staff on digital skills, provision of ICT knowledge for digital skills, access to computers among others are the possible solutions to the constraints affecting the utilization of technological facilities in teaching.
Keywords: Teaching and Learning; Technological Facilities; ICT Knowledge